Adherence to treatment in a Western European paediatric population with haemophilia: reliability and validity of the VERITAS‐Pro scale. (26th May 2014) - Lock, J.; Raat, H.; Duncan, N.; Shapiro, A.; Beijlevelt, M.; Peters, M.; Tamminga, R. Y. J.; Leebeek, F. W. G.; Moll, H. A.; Cnossen, M. H.
Summary: Treatment adherence in haemophilia is strongly associated with quality of life and the cost–benefit of treatment. Therefore, it is important to quantify and monitor it. This study aimed to validate a translation of the VERITAS‐Pro cross‐culturally and analyse treatment adherence in a Dutch population of paediatric haemophilia patients. Children aged 1–18 years with haemophilia were included from three Haemophilia Treatment Centres, on prophylactic clotting factor replacement therapy for more than 1 year. Parents and adolescents were analysed separately. The adherence scale for prophylactic therapy (VERITAS‐Pro) was translated according to international guidelines. This instrument contains a total of six subscales ('Time', 'Dose', 'Plan', 'Remember', 'Skip' and 'Communicate') each with four items. Lower scores reflect higher adherence. Overall response rate was 85%, leading to a study population of 60 children. Mean age was 10 years (SD 4.1). Internal consistency reliability : Mean Cronbach's alphas were adequate (>0.70) for total score and the subscales 'Skip' and 'Communicate'. Item‐own subscale correlations were stronger than most item‐other subscale correlations. Convergent validity : Total scores were higher for non‐adherent participants compared with adherent participants according to patient infusion logs ( n  = 48; P  <   0.05 ). Test–retest correlations: Significant for all scales except 'Dose' ( n  = 58; P  <   0.01). This study demonstrates applicability of VERITAS‐Pro outside the United States, as total score and most subscales effectively quantified treatment adherence in a Dutch paediatric population on prophylactic therapy. Non‐adherent respondents' total scores were significantly higher, demonstrating the ability of VERITAS‐Pro to identify non‐adherent individuals.